PENGARUH KUALITAS SERVICE TERHADAP KEPUASAN, KEPERCAYAAN, DAN KECENDERUNGAN BERPERILAKU MAHASISWA PADA PERGURUAN TINGGI DI JAKARTA - Primasatria Edastama (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2014)
Development and growth of universities in Jakarta encourage each university to achieve the best quality to get more students. This action need certain steps particularly by improve quality service. In this research will analyze the effect of service quality to students’ behavior intention, so university able to see the effect of quality service. The method in this study was Structural Equation Model(SEM), as subject research is students, and the data used primer data that collected by questionnaire. The result of this study showed a good service has effect to trust of behavior intention. However, this research also found the effect of satisfaction to trust is significant although it is weak effect, this also occur to the quality of service to trust and service quality. For the effect of quality service to behavior intention in this research showed strong effect. By the result of this research, it is hope that university able to manage the quality service better and more focus to student as customer because of tendency of their behavior.Keywords: service quality, trust, behavior intention